1997
DOI: 10.1111/j.1365-2044.1997.149-az0153.x
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of fluid around low‐pressure tracheal tube cuffs

Abstract: SummaryThe aim of the study was to evaluate leakage of liquid past the low-pressure cuffs of tracheal tubes. Ten samples of each of nine different types of tubes were tested in a PVC mock trachea, using intracuff pressures of 20, 30, 40 and 50 cmH 2 O. In five types of tubes, 6-10 cuffs allowed profuse leakage (> 20 ml water in 5 min) even at the highest intracuff pressure, i.e. 50 cmH 2 O. In the most efficient tube, all the cuffs were leak-proof (leakage < 5 ml in 5 min) at 40 cmH 2 O and in the second best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 7 publications
3
39
0
1
Order By: Relevance
“…This finding is consistent with previous studies [5,14]. However, the sealing effect of the Portex Profile tube hardly changed with the increase of intracuff pressure, suggesting that this tube may not be suitable for patients who are at risk of pulmonary aspiration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with previous studies [5,14]. However, the sealing effect of the Portex Profile tube hardly changed with the increase of intracuff pressure, suggesting that this tube may not be suitable for patients who are at risk of pulmonary aspiration.…”
Section: Discussionsupporting
confidence: 83%
“…One major drawback of such a cuff is that it does not effectively prevent leakage of fluid into the lower airway [5±8], since the diameter of the cuff is greater than that of the trachea and the cuff often makes longitudinal folds when inflated in the trachea. Nevertheless, there may be significant differences in the sealing effect between different types of high-volume, low-pressure cuffs [5]. It has been shown that in critically ill patients whose lungs are ventilated through a cuffed tracheal tube, one major source of pneumonitis is pulmonary aspiration of gastric contents [9,10].…”
mentioning
confidence: 99%
“…Bei invasiver Beatmung bildet der Endotrachealtubus eine Leitschiene für potenziell infektiöses Sekret aus dem Oropharynx [5]. Weil die bei nicht intubierten Gesunden bestehenden Schutzmechanismen wie Schluck-und Hustenreflexe und mukoziliäre Clearance gestört sind, führen diese Mikro aspirationen zu einem deutlich erhöhten Pneumonierisiko.…”
Section: Leitschiene Für Pathogene Aus Dem Oropharynxunclassified
“…25 However, even when the pressure in the HVLP cuff is increased to 50 cm H 2 O, aspiration of subglottic secretions can still occur through the development of channel formation because of folding in the cuff. 26,27 Secretions aspirated through the microchannels can eventually reach the lower respiratory tract and increase the risk of acquiring VAP. 26,27 It has been presumed that maintaining a cuff pressure that automatically adjusts to an adequate level may solve the problem.…”
Section: Cuff Pressurementioning
confidence: 99%
“…26,27 Secretions aspirated through the microchannels can eventually reach the lower respiratory tract and increase the risk of acquiring VAP. 26,27 It has been presumed that maintaining a cuff pressure that automatically adjusts to an adequate level may solve the problem. 28 However, a randomized controlled clinical trial that used continuous cuff pressure monitoring with continuous and constant cuff infl ation of 20 cm H 2 O showed no observed difference in VAP incidence when compared with routine care.…”
Section: Cuff Pressurementioning
confidence: 99%